2002
DOI: 10.1179/000349802125001249
|View full text |Cite
|
Sign up to set email alerts
|

The drug sensitivity and transmission dynamics of human malaria on Nias Island, North Sumatra, Indonesia

Abstract: Leksana, B.; Masbar, S.; Wiady, I.; Sismadi, P.; Susanti, A. I.; Nagesha, H. S.; Eijkman Institute for Molecular Biology; Atmosoedjono, S.; Bangs, M. J.; and Baird, J. Kevin, "The drug sensitivity and transmission dynamics of human malaria on Nias Island, North Sumatra, Indonesia" (2002). Public Health Resources. 421.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 31 publications
4
36
1
1
Order By: Relevance
“…Similar surveys in central and western Indonesia, however, revealed relatively low risk (<20%) [3,11-15]. The apparent isolation of high risk of CRPV to Indonesian New Guinea encouraged health authorities to maintain chloroquine as the national first-line therapy for vivax malaria.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar surveys in central and western Indonesia, however, revealed relatively low risk (<20%) [3,11-15]. The apparent isolation of high risk of CRPV to Indonesian New Guinea encouraged health authorities to maintain chloroquine as the national first-line therapy for vivax malaria.…”
Section: Discussionmentioning
confidence: 96%
“…Evidence from the western islands of Indonesia between 1992 until 1998, revealed relatively low risk (approx. 10%) of chloroquine- resistant P. vivax [3,11-15]. Nonetheless, in 2008 national treatment policy was changed to apply artesunate-amodiaquine as first-line therapy for vivax malaria throughout Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…However, all 38 subjects evaluated on a small, isolated island in Papua had infections with sensitive organisms (52). In western Indonesia two separate surveys at Nias, near northern Sumatra, found 9 inadequate responses among 49 subjects (18%) (16,50). A survey of 54 subjects in Indonesian Borneo revealed that 22% of the isolates were CRPV (53).…”
Section: Geographic Range Of Resistancementioning
confidence: 99%
“…8 Studies in Southeast Asia indicated that the rates of parasitologic failure at day 7 and day 28 were 36 percent and 49 percent, respectively. [74][75][76][77][78][79] Good efficacy (80 percent) persisted elsewhere -in southwestern Asia and on the Horn of Africa, where no parasitologic failures were reported among 362 evaluations 80,81 ; in southern Asia, where the failure rate was 18 percent (of 339 evaluations) by day 28 [55][56][57] ; and in South America, where the failure rate was 9 percent (of 50 evaluations) by day 7, 14 percent (of 42 evaluations) by day 14, and 6 percent (of 119 evaluations) by day 28. [82][83][84] The risk of resistance to sulfadoxine-pyrimethamine is relatively high in Southeast Asia and eastern Africa.…”
Section: Drug Resistancementioning
confidence: 99%